Selling a Rebellion: The Industrial Logic of Mainstream Alt-Porn - Moorman, Jennifer (Camera Obscura: Feminism, Culture, and Media Studies, 2017)
The seemingly paradoxical phenomenon of mainstream alt-porn belies ostensible distinctions between industrial pornography and its alternatives. These corporate iterations of alt-porn—an initially grassroots, oppositional, community-based form of adult filmmaking—tend to interweave the conventions and preoccupations of pornography and the avant-garde while straddling the mainstream and the margins of pornographic production. In exploring such liminal spaces, this article redresses the myopias both of rigidly anti-porn stances that fail to consider adult video's subversive potential, and of porn studies' tendency to elide analysis of mainstream texts. Extensive industrial immersion (including interviews with thirty-eight filmmakers and industry insiders) and textual analysis illuminate industrial praxis to argue that the seemingly rigid conventions and taxonomies of mainstream adult video are neither static nor stagnant but rather continually evolving. Despite ongoing blind spots, erasures, and systemic discrimination, the industry's output is increasingly diverse. This article explores mainstream alt-porn as a particularly productive site for locating ruptures, aporias, and outright challenges to industrial and generic hegemony. A series of case studies demonstrates that individual mainstream alt-porn films, despite their corporate production model, may not be antithetical to the subgenre's antiestablishment origins. Frequently adapting self-reflexive strategies from experimental filmmaking to evoke “critical arousal,” these alt-porn films revise, to varying extents, the representational politics of conventional adult video.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTIxNS8wMjcwNTM0Ni0zOTI0NjM5